A Work study on Giacomino's - Ng, May Antoniette R.; Santos, Vina Morena C. (Diliman, Quezon City College of Engineering, 1996)
The system investigated is a branch of Giacomino's at the Shangri-La Plaza, Fiesta Food Court. The activities examined were how the pizzas are being prepared by the crew and how these workers attend to the customers' orders. To promote efficiency, enhance service level, and maximize satisfaction of both customers and crew, Method Study tools and Work Measurement techniques were used. Consequently, the following suggestions were arrived at: (1) the existing layout should be rearranged; (2) locations of ingredients, materials and equipment on the racks, drawers, and storage counters should be fixed; (3) the display bin for the pasta products should be turned on; (4) in performing operations, the workers should follow the do-it-once principle when possible (e.g. taking out ingredients by batches); (5) for multiple orders, a standardized sequence of which order is to be served first should be followed by the crew; (6) the workers should utilize the inevitable idle time (e.g. folding pizza boxes); (7) a record form should replace the crude notebook system used for keeping track of the daily sales. Outweighing the costs of accomplishing the stated recommendations , the (qualitative and quantitative) benefits justify the implementation of these.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Giacomino's.; Pizza industry; Systems analysis